EFEKTIVITAS METODE PEMBELAJARAN PENDIDIKAN AGAMA ISLAM GUNA PENINGKATAN PEMAHAMAN PADA ANAK TUNA GRAHITA SLB NEGERI KOTA METRO - Nina Tisnawati; Ade Aulia Rahman (AT-TAJDID, 2018)
Islamic Religion Teachers are supervisors, therefore in the teaching and learning process there needs to be methods in accordance with their students. In learning Islamic Religion various methods were developed in educating students, educating mentally disabled children needed methods that are used specifically in each learning process, the problem we will discuss is how the effectiveness of the implementation of Islamic Education teacher teaching methods in the learning process in children mentally disabled people are at the Metro South State Metro School. The focus of research on the effectiveness of the implementation of Islamic Education teacher teaching methods in the teaching and learning process for mentally disabled children is at the Metro South State Metro School. The limitation of this problem is that in this study we will discuss the effectiveness of the implementation of Islamic Education teacher teaching methods in the teaching and learning process for mentally disabled children at the Metro South State Metro School. The purpose of this study was to determine the effectiveness of the teaching methods of teaching Islamic Education teachers in the teaching and learning process for mentally disabled children at the Metro South State Metro School. in developing various methods in the teaching and learning process, while practically this research can provide input for Islamic education teachers at the Special Schools in the Southern City of Metro in effective learning. The method used in this study is an unstructured interview method, then the researcher uses unstructured observation methods. what the research did in this case was to observe directly the teaching and learning process in the classroom and outside the classroom, another method that researchers used was the method of documentation as a support in this study.